2011
DOI: 10.1159/000322574
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Retention in the ‘Voluntary’ and ‘Quasi-Compulsory’ Treatment of Substance Dependence in Europe

Abstract: Background: Policies and practices related to the quasi-compulsory treatment (QCT) of substance-dependent offenders are currently implemented in many countries, despite the absence of reliable knowledge about significant predictors of treatment retention. This study aimed to identify such predictors in QCT and voluntary treatment. Methods: Participants were treated in one of 65 institutions in 5 European countries. They were interviewed at intake on substance use, crimes committed, perceived pressure for treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Session attendance was similar to our prior treatment study with adults with co-occurring depression and substance use disorders who received group-delivered sessions in both phases of treatment (Drapkin et al, 2008). In general, the low rates of attendance found in our study were consistent with previous research that has found attrition to be a significant barrier to mental health treatment (Dutra et al, 2008; Curran et al, 2002; Schaub et al, 2011; Roberts et al, 2015; Spinazzola et al, 2005). …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Session attendance was similar to our prior treatment study with adults with co-occurring depression and substance use disorders who received group-delivered sessions in both phases of treatment (Drapkin et al, 2008). In general, the low rates of attendance found in our study were consistent with previous research that has found attrition to be a significant barrier to mental health treatment (Dutra et al, 2008; Curran et al, 2002; Schaub et al, 2011; Roberts et al, 2015; Spinazzola et al, 2005). …”
Section: Discussionsupporting
confidence: 92%
“…A number of psychotherapy studies including our prior treatment study have found that predisposing factors of younger age, minority status, and polysubstance use were associated with lower treatment retention (Barrett et al, 2008; Schaub et al, 2011; Tate et al, 2011) and several addictions studies had similar findings with regard to predisposing factors of being female, having less years of education, and having cognitive impairments (Aharonovich et al, 2006; Brady, Dansky, Back, Foa, & Carroll, 2001; Sayre et al, 2002). Our study did not find any other predisposing factors including age, ethnicity, and type of substance use disorder to be associated with treatment attendance.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…51 However, when people are ready to change and perceive a medical necessity, and effective therapies are accessible, they see a stronger incentive to engage and remain in treatment than through legal pressure. 52 Efficient coordination between treatment providers and police or courts can facilitate better access to treatment and improve outcomes. 53 In recent years, several Asian countries have begun moving to voluntary centres providing comprehensive evidence based treatment and support services.…”
Section: Mandatory Treatment-from Detention To Cooperationmentioning
confidence: 99%